Search for Loyal People: On the Assessment of One 1939 Report by the State Security Department - Kaubrys, Saulius (Lietuvos istorijos studijos, 2016)
Consideration of the development of the fate of the communities of national minorities is on the agenda of the present-day Lithuanian historiography and arouses considerable interest. This attempt is related to the aspiration to go deeper into the ins and outs of the development of the German community in Lithuania. The aim of this article is to reveal the characteristics of the fairly statistically fixed metric of the said community of 1938, collected by way of watching it. Lithuanian special operational services collected information about the moods prevailing in the groups of national minorities on a regular basis, and the German case was no exception. A secret certificate of the State Security Department of 1 March 1939 contained a survey of the 1938 cultural and economic situation of the Lithuanian Germans. The latter data summary contains the information about the German organisational structures (public organisations, confessional formations, establishments of institutional education and economic activities of the Germans (factories, enterprises, shops, mills, saw-mills and others, as well as independent agricultural entities). The author of the article, assessing the whole complex of loyalty characteristics recorded in the summary (the owners and their subordinates are referred to as loyal and disloyal, though, unfortunately, the data are incomplete) and applying the logistic regression model vhich established that chances of loyalty of the German women were greater than those of the German men. During the investigations, the present author was able to establish that chances of loyalty of the German community in southern Lithuania were slightest (they could have been determined by the factor of the border with Germany), and the highest chances of loyalty arose in the case of the German community in Central Lithuania. In the opinion of the present author, the ratio of persons belonging to another nation and the Germans on a defined territory also exerted influence on the characteristics of loyalty.